Análise das propriedades dinâmicas e estruturais da água confinada entre placas hidrofóbicas - Kipper, Ana Claudia (2013)
In this work we studied the properties of confined water by graphene sheets via Classical Molecular Dynamics. The main objective of this dissertation is to understand how the structural and dynamic properties of confined water can be changed due to the geometric confinement, including the density profile, formation of layering, the average number of hydrogen bonds and the diffusion process of water molecules. The confinement geometry is formed by two graphene sheets aligned parallel with respect to one another separated by a distance "d". Both the distance "d" as the system temperature were varied to obtain different degrees of confinement and thermodynamic conditions. Values used were d=7, 9, 11, 15, 20, 25 and 30Å and T=280, 300 and 320K. Furthermore, all simulations were carried out with GROMACS (GROningen Machine for Chemical Simulations) code in a NVT ensemble (particle number, volume and pressure are kept constant) and using SPC/E (Simple Point Charge/Extend) water model. For these systems have been found that confinement induces the formation of layers of water molecules and the number of layers depend on the degree of confinement. Due to this structure, we analyzed the average number of hydrogen bonds with water molecules and these molecules in the respective diffusion layers (central and near the confining walls). It was concluded that the formation of layers is directly related to the breaking of hydrogen bonds.